Phylogenetic analysis of anaerobic thermophilic bacteria: aid for their reclassification. - Rainey, F A (1993)
Small subunit rDNA sequences were determined for 20 species of the genera Acetogenium, Clostridium, Thermoanaerobacter, Thermoanaerobacterium, Thermoanaerobium, and Thermobacteroides, 3 non-validly described species, and 5 isolates of anaerobic thermophilic bacteria, providing a basis for a phylogenetic analysis of these organisms. Several species contain a version of the molecule significantly longer than that of Escherichia coli because of the presence of inserts. On the basis of normal evolutionary distances, the phylogenetic tree indicates that all bacteria investigated in this study with a maximum growth temperature above 65 degrees C form a supercluster within the subphylum of gram-positive bacteria that also contains Clostridium thermosaccharolyticum and Clostridium thermoaceticum, which have been previously sequenced. This supercluster appears to be equivalent in its phylogenetic depth to the supercluster of mesophilic clostridia and their nonspore-forming relatives. Several phylogenetically and phenotypically coherent clusters that are defined by sets of signature nucleotides emerge within the supercluster of thermophiles. Clostridium thermobutyricum and Clostridium thermopalmarium are members of Clostridium group I. A phylogenetic tree derived from transversion distances demonstrated the artificial clustering of some organisms with high rDNA G+C moles percent, i.e., Clostridium fervidus and the thermophilic, cellulolytic members of the genus Clostridium. The results of this study can be used as an aid for future taxonomic restructuring of anaerobic sporogenous and asporogenous thermophillic, gram-positive bacteria.